Bureaucratic Technologies and Political Subjects: Records in Indian Police Procedure and Corporate Customer Service - Hull, Matthew S. (Contributions to Indian sociology, 2023)
In 2013, the Indian state of Punjab contracted with a corporation to operate a new police phone helpline. The corporation call centre not only electronically logged complaints, but also monitored, directed and reported police responses to them. We can see in this arrangement two parallel tensions.The first tension is between two different forms of human and technological mediation: the paper-based records of police and the voice and electronic database records of the call centre. This parallels a tension between two constructions of a political subject in bureaucratic practices: (a) the first requires that a person be represented by an authoritative official of the state and is codified in police law, and (b) the second, enacted in customer service practices, requires that a person represent him or herself, that is, with minimal agential involvement of another person.